Influence of Marketing-Mix on Purchase Decision at JNE - Pristanto Ria Irawan; Pupung Purnamasari; Darka; Dadang Heri Kusumah; Ismasari Nawangsih; Noorevna Ayaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the extent to which the marketing mix, purchasing decisions, and the influence of the marketing mix on purchasing decisions at PT. Jalur Nugraha Ekakurir in Kemayoran Area.This study uses a quantitative descriptive method with data collection techniques through the distribution of questionnaires and library data. In this study, the sample used was 60 customers. The data analysis technique used is simple linear regression analysis using the SPSS application.The variable marketing mix is quite good, amounting to 65.25 lies in the interval 63.2 - 67.2 variable purchasing decision is quite good at 30.42 located in the class interval 29.8 - 31.6 and (3) There is an influence between the marketing mix variable the purchasing decision because the value of t count (9.211) is greater than the value of t table (1.623) so that H1 is accepted and the t-count value lies in the rejection area of H0 or H1 is accepted. Then the marketing mix positive influence on strong the r value of 0.771 (located in the correlation coefficient interval 0.60-0.799) and has an influence contribution of 59.4% on the purchasing decision variable, while the remaining 40.6% is influenced by other factors. . Furthermore, it can be seen that the regression equation that can be used to predict is Y' = 4.577 + 0.396 X